Steel wire
Patent Information
- Application Number
- JP2023115725
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
AI Technical Summary
【0012】 本開示の鋼線は、高い引張強さと優れた耐久比とを有する。
Smart Images

Figure 2025012690000001 
Figure 2025012690000002 
Figure 2025012690000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a steel wire. [Background technology]
[0002] Steel wires are used for beads in automobile tires, wire ropes in bridges, wire ropes in elevators, PC steel wires, hard steel wires for power transmission, etc. High tensile strength is required for steel wires used for these applications. Meanwhile, in the usage environment of steel wires, they are repeatedly subjected to changes in the stress state. Examples of changes in the stress state include a change from high tensile stress to low tensile stress, or a change from tensile stress to compressive stress. Therefore, high fatigue strength is required for steel wires.
[0003] Steel wires having high tensile strength or high tensile strength and high fatigue strength have been proposed in JP-A-10-305308 (Patent Document 1) and JP-A-6-49592 (Patent Document 2).
[0004] The steel wire disclosed in Patent Document 1 contains C: 0.70% or more and less than 1.00%, has a Vickers hardness difference between the C-section surface layer and the center of less than 100, a tensile strength of 2000 MPa or more, and an elongation of 6% or more. In this steel wire, the die approach angle and the area reduction rate per die in the wire drawing process are optimized, and further, the final die is rotated or bent to improve the elongation characteristics and strength.
[0005] The steel wire disclosed in Patent Document 2 contains, by weight, C: 0.80-1.10%, Si: 0.25% or less, Mn: 0.45% or less, P: 0.010% or less, S: 0.010% or less, Cr: 0.15-0.35%, N: 0.0040% or less, and B: (0.0005-0.01)×Cr[%]+0.001%, with the balance being Fe and unavoidable impurities. This steel wire is drawn while suppressing the occurrence of microdefects at the ferrite-cementite interface, thereby improving strength and fatigue properties. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 10-305308 [Patent Document 2] Japanese Patent Application Publication No. 6-49592 [Non-patent literature]
[0007] [Non-Patent Document 1] Tomoda et al., "Recent Advances in Neutron and X-ray Diffraction Line Profile Analysis," Iron and Steel, Vol. 103 (2017) No. 2, pp. 73-85 [Non-Patent Document 2] Takagi et al., "Evaluation of dislocation density in cold-worked low-carbon ferritic steels," Tetsu-to-Haganen, Vol. 104 (2018) No. 11, pp. 683-688. Summary of the Invention [Problem to be solved by the invention]
[0008] However, the tensile strength and durability ratio of the steel wire may be increased by other means different from those proposed in Patent Documents 1 and 2.
[0009] An object of the present disclosure is to provide a steel wire having high tensile strength and excellent durability ratio. [Means for solving the problem]
[0010] The steel wire according to the present disclosure comprises: Chemical composition, in mass%, C: less than 0.70 to 1.10% Si: 0.10 to 1.00%, Mn: 0.20-1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, and N: 0.0100% or less, The balance is Fe and impurities. The tensile strength is 1600 to 2500 MPa. The screw dislocation ratio is 0.60 or more.
[0011] The steel wire according to the present disclosure comprises: Chemical composition, in mass%, C: less than 0.70 to 1.10% Si: 0.10 to 1.00%, Mn: 0.20-1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, and N: 0.0100% or less, Further, the composition contains one or more selected from the group consisting of group 1 and group 2, The balance is Fe and impurities. The tensile strength is 1600 to 2500 MPa. The screw dislocation ratio is 0.60 or more. [Group 1] Cr: 0.50% or less, Co: 0.50% or less, Cu: 0.50% or less, Ni: 0.50% or less, Mo: 0.20% or less B: 0.0050% or less, W: 0.20% or less, Ti: 0.100% or less, Nb: 0.100% or less, Sn: 0.100% or less, and V: 0.10% or less, one or more selected from the group consisting of [Group 2] Ca: 0.0050% or less, Mg: 0.0050% or less, Zr: 0.010% or less, and Rare earth elements (REM): 0.005% or less, one or more selected from the group consisting of Effect of the Invention
[0012] The steel wire of the present disclosure has high tensile strength and excellent durability ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present inventors have conducted research into steel wires having high tensile strength and excellent durability ratio, and as a result, have made the following discoveries.
[0014] The present inventors first investigated a steel wire having high tensile strength from the viewpoint of chemical composition. As a result, the following composition was obtained by mass %: C: 0.70 to less than 1.10%, Si: 0.10 to 1.00%, Mn: 0.20 to 1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, N: 0.0100% or less, Cr: 0 to 0.50%, Co: 0 to 0.50%, Cu: 0 to 0.50%, Ni: 0 to 0.50%, Mo: 0 to 0.20%, B: 0 to 0.005%. It was thought that a steel wire having a chemical composition consisting of 0%, W: 0-0.20%, Ti: 0-0.100%, Nb: 0-0.100%, Sn: 0-0.100%, V: 0-0.10%, Ca: 0-0.0050%, Mg: 0-0.0050%, Zr: 0-0.010%, rare earth elements (REM): 0-0.005%, and the balance being Fe and impurities would have a tensile strength of 1600-2500 MPa.
[0015] Therefore, the present inventors further studied means for increasing the durability ratio of a steel wire having the above-mentioned chemical composition. Here, the present inventors focused on the behavior of dislocations in a steel wire under repeated stress. Dislocations include edge dislocations and screw dislocations. Edge dislocations are more energetically unstable than screw dislocations. Therefore, edge dislocations move more easily than screw dislocations. When dislocations move, positive and negative dislocations may pair up and disappear. When edge dislocations repeatedly move and disappear under repeated stress, the dislocation density decreases, and as a result, the durability ratio decreases.
[0016] Based on the above findings, the inventors considered that the durability ratio would be increased if the proportion of screw dislocations among the dislocations in the steel wire was increased in advance. As described above, screw dislocations are more energetically stable than edge dislocations. Therefore, screw dislocations are less likely to move even under repeated stress. If the proportion of screw dislocations is high, the proportion of dislocations that are less likely to move under repeated stress increases. Therefore, it is possible to reduce the frequency with which dislocations disappear due to movement. As a result, the durability ratio is increased.
[0017] Based on the above findings, the present inventors have investigated the appropriate screw dislocation ratio in a steel wire having the above-mentioned chemical composition and a tensile strength of 1600 to 2500 MPa. The method of deriving the screw dislocation ratio will be described later. As a result of the investigation, it was found that if the screw dislocation ratio is 0.60 or more, an excellent durability ratio can be obtained even if the tensile strength is 1600 to 2500 MPa.
[0018] The steel wire according to the present embodiment, which has been completed based on the above findings, has the following configuration.
[0019] [1] Chemical composition, in mass%, C: less than 0.70 to 1.10% Si: 0.10 to 1.00%, Mn: 0.20-1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, and N: 0.0100% or less, The balance is Fe and impurities. The tensile strength is 1600 to 2500 MPa. The screw dislocation ratio is 0.60 or more. Steel wire.
[0020] [2] Chemical composition, in mass%, C: less than 0.70 to 1.10% Si: 0.10 to 1.00%, Mn: 0.20-1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, and N: 0.0100% or less, Further, the composition contains one or more selected from the group consisting of group 1 and group 2, The balance is Fe and impurities. The tensile strength is 1600 to 2500 MPa. The screw dislocation ratio is 0.60 or more. Steel wire. [Group 1] Cr: 0.50% or less, Co: 0.50% or less, Cu: 0.50% or less, Ni: 0.50% or less, Mo: 0.20% or less B: 0.0050% or less, W: 0.20% or less, Ti: 0.100% or less, Nb: 0.100% or less, Sn: 0.100% or less, and V: 0.10% or less, one or more selected from the group consisting of [Group 2] Ca: 0.0050% or less, Mg: 0.0050% or less, Zr: 0.010% or less, and Rare earth elements (REM): 0.005% or less, one or more selected from the group consisting of
[0021] [3] [2] A steel wire according to the present invention, The chemical composition contains the first group, Steel wire.
[0022] [4] The steel wire according to [2] or [3], The chemical composition contains the second group, Steel wire.
[0023] The steel wire according to the present embodiment will be described in detail below. Note that "%" for elements means mass % unless otherwise specified.
[0024] [Features of the steel wire according to this embodiment] The steel wire of the present embodiment satisfies the following Features 1 to 3. (Feature 1) Chemical composition, by mass%, is C: 0.70-1.10%, Si: 0.10-1.00%, Mn: 0.20-1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, N: 0.0100% or less, Cr: 0-0.50%, Co: 0-0.50%, Cu: 0-0.50%, Ni: 0-0.50%. , Mo: 0-0.20%, B: 0-0.0050%, W: 0-0.20%, Ti: 0-0.100%, Nb: 0-0.100%, Sn: 0-0.100%, V: 0-0.10%, Ca: 0-0.0050%, Mg: 0-0.0050%, Zr: 0-0.010%, rare earth elements (REM): 0-0.005%, and the balance is Fe and impurities. (Feature 2) The tensile strength is 1600 to 2500 MPa. (Feature 3) The screw dislocation ratio is 0.60 or more. Features 1 to 3 will be explained below.
[0025] [(Feature 1) Chemical composition] The chemical composition of the steel wire of this embodiment contains the following elements.
[0026] C: 0.70 to less than 1.10% Carbon (C) increases the strength of the steel wire. If the C content is less than 0.70%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the C content is 1.10% or more, pro-eutectoid cementite is excessively formed. In this case, the toughness and ductility of the steel wire are reduced. Therefore, the C content is 0.70 to less than 1.10%. The lower limit of the C content is preferably 0.74%, more preferably 0.78%, and further preferably 0.80%. The upper limit of the C content is preferably 1.08%, more preferably 1.05%, and further preferably 1.00%.
[0027] Silicon: 0.10 to 1.00% Silicon (Si) increases the strength of the steel wire. Furthermore, Si deoxidizes the steel in the steelmaking process in the manufacturing process of the steel wire. If the Si content is less than 0.10%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Si content exceeds 1.00%, Si dissolves excessively in ferrite, and wiredrawability is reduced. Therefore, the Si content is 0.10 to 1.00%. The lower limit of the Si content is preferably 0.15%, more preferably 0.20%, and further preferably 0.25%. The upper limit of the Si content is preferably 0.95%, more preferably 0.90%, and further preferably 0.85%.
[0028] Mn: 0.20-1.00% Manganese (Mn) improves the hardenability and increases the strength of the steel wire. Mn also fixes S in the steel material and improves the hot workability of the wire material. If the Mn content is less than 0.20%, the above effects cannot be sufficiently obtained. On the other hand, if the Mn content exceeds 1.00%, Mn segregates in the steel wire. In this case, martensite or bainite is formed in the region where Mn is segregated, and the wire drawability of the wire material decreases. Therefore, the Mn content is 0.20 to 1.00%. The lower limit of the Mn content is preferably 0.25%, more preferably 0.30%, and further preferably 0.35%. The upper limit of the Mn content is preferably 0.95%, more preferably 0.90%, and further preferably 0.85%.
[0029] P:0.020% or less Phosphorus (P) is an impurity. If the P content exceeds 0.020%, P segregates at the grain boundaries. This embrittles the grain boundaries and reduces the drawability of the wire rod that is the raw material for steel wire. Therefore, the P content is set to 0.020% or less. It is preferable that the P content is as low as possible. However, excessive reduction in the P content increases the production cost. Therefore, in consideration of normal industrial production, the preferable lower limit of the P content is more than 0%, more preferably 0.001%, more preferably 0.003%, and even more preferably 0.005%. The upper limit of the P content is preferably 0.018%, more preferably 0.016%, and further preferably 0.014%.
[0030] S: 0.020% or less Sulfur (S) is an impurity. If the S content exceeds 0.020%, S will segregate at grain boundaries. Furthermore, excessive amounts of coarse MnS will be produced. This will result in a decrease in the drawability of the wire rod that is the raw material for steel wire. Therefore, the S content must be 0.020% or less. The S content is preferably as low as possible. However, excessive reduction in the S content increases the production cost. Therefore, in consideration of normal industrial production, the preferred lower limit of the S content is more than 0%, more preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%. The upper limit of the S content is preferably 0.018%, more preferably 0.016%, and further preferably 0.014%.
[0031] Al: 0.080% or less Aluminum (Al) deoxidizes steel. However, if the Al content exceeds 0.080%, excessive coarse oxides are generated. In this case, the wire drawability of the wire rod that is the raw material for steel wire is reduced. Therefore, the Al content is 0.080% or less. The lower limit of the Al content is preferably more than 0%, more preferably 0.001%, further preferably 0.002%, and further preferably 0.003%. The upper limit of the Al content is preferably 0.070%, more preferably 0.060%, and further preferably 0.050%.
[0032] O: 0.0050% or less Oxygen (O) is an impurity. If the O content exceeds 0.0050%, coarse oxides are formed in the steel wire, and the fatigue strength of the steel wire decreases. Therefore, the O content is 0.0050% or less. The O content is preferably as low as possible. However, excessive reduction in the O content increases the production cost. Therefore, in consideration of normal industrial production, the lower limit of the O content is preferably more than 0%, more preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.0005%. The upper limit of the O content is preferably 0.0030%, and more preferably 0.0020%.
[0033] N: 0.0100% or less Nitrogen (N) is an impurity. If the N content exceeds 0.0100%, excessive nitrides are formed. In this case, the wire drawability of the wire rod that is the raw material for steel wire decreases. Therefore, the N content is 0.0100% or less. The lower limit of the N content is preferably more than 0%, more preferably 0.0001%, still more preferably 0.0002%, and still more preferably 0.0005%. The upper limit of the N content is preferably 0.0090%, more preferably 0.0080%, and further preferably 0.0070%.
[0034] The balance of the chemical composition of the steel wire according to the present embodiment is composed of Fe and impurities. Here, the impurities in the chemical composition refer to those that are mixed in from raw materials such as ore and scrap, or the manufacturing environment, during industrial production of the steel wire, and are unintentionally contained and are permissible within a range that does not adversely affect the steel wire according to the present embodiment.
[0035] [About optional elements] The chemical composition of the steel wire of the present embodiment may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of a first group and a second group.
[0036] [Group 1] Cr: 0.50% or less, Co: 0.50% or less, Cu: 0.50% or less, Ni: 0.50% or less, Mo: 0.20% or less B: 0.0050% or less, W: 0.20% or less, Ti: 0.100% or less, Nb: 0.100% or less, Sn: 0.100% or less, and V: 0.10% or less, one or more selected from the group consisting of [Group 2] Ca: 0.0050% or less, Mg: 0.0050% or less, Zr: 0.010% or less, and Rare earth elements (REM): 0.005% or less, one or more selected from the group consisting of These optional elements will now be described.
[0037] [Group 1: Cr, Co, Cu, Ni, Mo, B, W, Ti, Nb, Sn and V] The chemical composition of the steel wire of the present embodiment may further contain the above-mentioned elements of Group 1 in place of a portion of Fe. These elements are optional elements, and all of them improve the hardenability and increase the strength of the steel wire.
[0038] Cr:0.50% or less Chromium (Cr) is an optional element and may not be contained. In other words, the Cr content may be 0%. When contained, that is, when the Cr content is more than 0%, Cr improves hardenability and increases the strength of the steel wire. Even if even a small amount of Cr is contained, the above effects can be obtained to some extent. However, when the Cr content exceeds 0.50%, the transformation end time becomes longer and supercooled structures such as martensite and bainite are likely to occur in the wire rod during hot rolling. Therefore, the Cr content is 0 to 0.50%, and when contained, it is 0.50% or less. The lower limit of the Cr content is preferably 0.01%, more preferably 0.05%, and further preferably 0.08%. The upper limit of the Cr content is preferably 0.45%, more preferably 0.40%, and further preferably 0.35%.
[0039] Co:0.50% or less Cobalt (Co) is an optional element and may not be contained. In other words, the Co content may be 0%. When it is contained, that is, when the Co content is more than 0%, Co improves the hardenability and increases the strength of the steel wire. Even if even a small amount of Co is contained, the above effects can be obtained to a certain extent. However, when the Co content exceeds 0.50%, the wire drawability of the wire rod that is the raw material for the steel wire decreases. Therefore, the Co content is 0 to 0.50%, and when it is contained, it is 0.50% or less. The lower limit of the Co content is preferably 0.01%, more preferably 0.05%, and further preferably 0.08%. The upper limit of the Co content is preferably 0.45%, more preferably 0.40%, and further preferably 0.35%.
[0040] Cu: 0.50% or less Copper (Cu) is an optional element and may not be contained. In other words, the Cu content may be 0%. When copper is contained, that is, when the Cu content is more than 0%, Cu improves hardenability and increases the strength of the steel wire. Even if even a small amount of Cu is contained, the above effects can be obtained to a certain extent. However, when the Cu content exceeds 0.50%, the wiredrawability of the wire rod that is the raw material for the steel wire decreases. Therefore, the Cu content is 0 to 0.50%, and when copper is contained, it is 0.50% or less. The lower limit of the Cu content is preferably 0.01%, more preferably 0.05%, and further preferably 0.08%. The upper limit of the Cu content is preferably 0.45%, more preferably 0.40%, and further preferably 0.35%.
[0041] Ni: 0.50% or less Nickel (Ni) is an optional element and may not be contained. In other words, the Ni content may be 0%. When nickel is contained, that is, when the Ni content is more than 0%, Ni delays the transformation of pro-eutectoid cementite and grain boundary ferrite during cooling from the austenite temperature range in the manufacturing process of the steel wire. This causes fine pearlite lamellae to be formed. As a result, the strength of the steel wire is increased while adequately maintaining the wiredrawability of the wire rod that is the raw material of the steel wire. If even a small amount of Ni is contained, the above effect can be obtained to some extent. However, if the Ni content exceeds 0.50%, the hardenability becomes excessively high. In this case, bainite is formed in the wire rod, and the wiredrawability of the wire rod decreases. Therefore, the Ni content is 0 to 0.50%, and when contained, it is 0.50% or less. The lower limit of the Ni content is preferably 0.01%, more preferably 0.02%, and further preferably 0.05%. The upper limit of the Ni content is preferably 0.45%, more preferably 0.40%, and further preferably 0.35%.
[0042] Mo: 0.20% or less Molybdenum (Mo) is an optional element and may not be contained, that is, the Mo content may be 0%. When contained, that is, when the Mo content exceeds 0%, Mo improves the hardenability of the steel wire and increases the strength of the steel wire. Even if even a small amount of Mo is contained, the above effects can be obtained to a certain extent. However, if the Mo content exceeds 0.20%, the hot workability of the steel material decreases in the manufacturing process of the steel wire even if the contents of other elements are within the ranges of this embodiment. Therefore, the Mo content is 0 to 0.20%, and if contained, it is 0.20% or less. The lower limit of the Mo content is preferably 0.01%, more preferably 0.02%, and further preferably 0.05%. The upper limit of the Mo content is preferably 0.18%, more preferably 0.17%, and further preferably 0.16%.
[0043] B: 0.0050% or less Boron (B) is an optional element and may not be contained. In other words, the B content may be 0%. When contained, that is, when the B content is more than 0%, B improves hardenability and increases the strength of the steel wire. Even if even a small amount of B is contained, the above effects can be obtained to a certain extent. However, when the B content exceeds 0.0050%, the hot workability of the steel material that is the raw material of the steel wire is reduced in the manufacturing process of the steel wire. Therefore, the B content is 0 to 0.0050%, and when contained, it is 0.0050% or less. The lower limit of the B content is preferably 0.0001%, and more preferably 0.0002%. The upper limit of the B content is preferably 0.0040%, and more preferably 0.0030%.
[0044] W: 0.20% or less Tungsten (W) is an optional element and may not be contained. In other words, the W content may be 0%. When it is contained, that is, when the W content is more than 0%, W improves the hardenability and increases the strength of the steel wire. Even if even a small amount of W is contained, the above effects can be obtained to a certain extent. However, when the W content exceeds 0.20%, the hot workability of the steel material decreases in the manufacturing process of the steel wire. Therefore, the W content is 0 to 0.20%, and when it is contained, it is 0.20% or less. The lower limit of the W content is preferably 0.01%, more preferably 0.03%, and further preferably 0.05%. The upper limit of the W content is preferably 0.18%, more preferably 0.16%, and further preferably 0.14%.
[0045] Ti:0.100% or less Titanium (Ti) is an optional element and may not be contained. In other words, the Ti content may be 0%. When titanium is contained, that is, when the Ti content is more than 0%, Ti improves hardenability and increases the strength of the steel wire. Even if even a small amount of Ti is contained, the above effects can be obtained to a certain extent. However, when the Ti content exceeds 0.100%, the hot workability of the steel material is reduced in the manufacturing process of the steel wire. Therefore, the Ti content is 0 to 0.100%, and when contained, it is 0.100% or less. The lower limit of the Ti content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%. The upper limit of the Ti content is preferably 0.090%, more preferably 0.080%, and further preferably 0.070%.
[0046] Nb: 0.100% or less Niobium (Nb) is an optional element and may not be contained. In other words, the Nb content may be 0%. When contained, that is, when the Nb content is more than 0%, Nb improves hardenability and increases the strength of the steel wire. Even if even a small amount of Nb is contained, the above effects can be obtained to a certain extent. However, when the Nb content exceeds 0.100%, the hot workability of the steel material is reduced in the manufacturing process of the steel wire. Therefore, the Nb content is 0 to 0.100%, and when contained, it is 0.100% or less. The lower limit of the Nb content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%. The upper limit of the Nb content is preferably 0.090%, more preferably 0.070%, and further preferably 0.050%.
[0047] Sn: 0.100% or less Tin (Sn) is an optional element and may not be contained. In other words, the Sn content may be 0%. When it is contained, that is, when the Sn content is more than 0%, Sn suppresses ferrite decarburization that occurs during hot working and suppresses a decrease in the strength of the steel wire. If even a small amount of Sn is contained, the above effect can be obtained to a certain extent. However, if the Sn content exceeds 0.100%, Sn segregates at grain boundaries and red embrittlement occurs even if the contents of other elements are within the range of this embodiment. In this case, the hot workability of the steel material that is the raw material for the steel wire is reduced. Therefore, the Sn content is 0 to 0.100%, and when it is contained, it is 0.100% or less. The lower limit of the Sn content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%. The upper limit of the Sn content is preferably 0.090%, more preferably 0.070%, and further preferably 0.050%.
[0048] V:0.10% or less Vanadium (V) is an optional element and may not be contained. In other words, the V content may be 0%. When it is contained, that is, when the V content is more than 0%, V improves the hardenability and increases the strength of the steel wire. Even if even a small amount of V is contained, the above effects can be obtained to a certain extent. However, when the V content exceeds 0.10%, the wiredrawability of the wire rod that is the raw material for the steel wire decreases. Therefore, the V content is 0 to 0.10%, and when it is contained, it is 0.10% or less. The lower limit of the V content is preferably 0.01%, more preferably 0.02%, and further preferably 0.03%. The upper limit of the V content is preferably 0.09%, more preferably 0.08%, and further preferably 0.07%.
[0049] [Group 2: Ca, Mg, Zr and rare earth elements (REM)] The chemical composition of the steel wire of the present embodiment may further contain the above-mentioned elements of Group 2 in place of a portion of Fe. These elements are optional elements, and all of them increase the ductility of the steel wire.
[0050] Ca: 0.0050% or less Calcium (Ca) is an optional element and may not be contained. In other words, the Ca content may be 0%. When contained, that is, when the Ca content is more than 0%, Ca reduces hard alumina-based inclusions and increases the ductility of the wire rod that is the raw material for the steel wire. Even if even a small amount of Ca is contained, the above effects can be obtained to a certain extent. However, when the Ca content exceeds 0.0050%, coarse oxides are generated. In this case, the wiredrawability of the wire rod decreases. Therefore, the Ca content is 0 to 0.0050%, and when contained, it is 0.0050% or less. The lower limit of the Ca content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0010%. The upper limit of the Ca content is preferably 0.0045%, more preferably 0.0040%, and further preferably 0.0030%.
[0051] Mg: 0.0050% or less Magnesium (Mg) is an optional element and may not be contained. In other words, the Mg content may be 0%. When magnesium is contained, that is, when the Mg content is more than 0%, Mg forms fine oxides. The fine oxides refine the structure of the steel wire and increase the ductility of the wire rod that is the raw material for the steel wire. Even if even a small amount of Mg is contained, the above effects can be obtained to a certain extent. However, when the Mg content exceeds 0.0050%, coarse oxides are generated, and the wire drawability of the wire rod decreases. Therefore, the Mg content is 0 to 0.0050%, and when contained, it is 0.0050% or less. The lower limit of the Mg content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0010%. The upper limit of the Mg content is preferably 0.0045%, more preferably 0.0040%, and further preferably 0.0030%.
[0052] Zr: 0.010% or less Zirconium (Zr) is an optional element and may not be contained. In other words, the Zr content may be 0%. When contained, that is, when the Zr content is more than 0%, Zr forms fine oxides. The fine oxides refine the structure of the steel wire and increase the ductility of the steel wire. If even a small amount of Zr is contained, the above effect can be obtained to some extent. However, if the Zr content exceeds 0.010%, even if the contents of other elements are within the range of this embodiment, coarse oxides are generated, and the wire drawability of the wire material of the steel wire is reduced. Therefore, the Zr content is 0 to 0.010%, and when contained, it is 0.010% or less. The lower limit of the Zr content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the Zr content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.
[0053] Rare earth elements: 0.005% or less Rare earth elements (REM) are optional elements and may not be contained. In other words, the REM content may be 0%. When contained, that is, when the REM content is more than 0%, REM forms fine sulfides and renders S harmless. This increases the ductility of the steel wire. Even if even a small amount of REM is contained, the above effects can be obtained to some extent. However, when the REM content exceeds 0.005%, coarse oxides are generated, which reduces the wire drawability of the wire rod that is the raw material for the steel wire. Therefore, the REM content is 0 to 0.005%, and when contained, it is 0.005% or less. The lower limit of the REM content is preferably 0.001%, and more preferably 0.002%. A preferred upper limit for the REM content is 0.004%.
[0054] In this specification, REM refers to one or more elements selected from the group consisting of scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and the lanthanides lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. In addition, in this specification, the REM content refers to the total content of these elements.
[0055] [Feature 2: Tensile strength] The steel wire according to this embodiment has a tensile strength of 1600 to 2500 MPa. Although the steel wire according to this embodiment has such a high tensile strength, it also has an excellent durability ratio by satisfying the following characteristic 3.
[0056] The lower limit of the tensile strength is preferably 1650 MPa, and more preferably 1700 MPa. The upper limit of the tensile strength is preferably 2450 MPa, and more preferably 2400 MPa.
[0057] [Method of measuring tensile strength] In this embodiment, the tensile strength can be determined by the following method. A tensile test is performed in air at room temperature (20±15°C) in accordance with JIS Z 2241:2022 to obtain the tensile strength (MPa). The tensile test specimen is taken so that the longitudinal direction is the axial direction of the steel wire. The test is performed three times, and the arithmetic average value is the tensile strength of the steel wire.
[0058] [(Feature 3) Screw dislocation ratio] Furthermore, in the steel wire of this embodiment, the screw dislocation ratio is 0.60 or more. Screw dislocations have lower mobility than edge dislocations. Therefore, under repeated stress, screw dislocations are less likely to move than edge dislocations. Therefore, even under repeated stress, the dislocation density in the steel wire is maintained. As a result, the durability ratio of the steel wire is increased. When the screw dislocation ratio is 0.60 or more, the steel wire has an excellent durability ratio.
[0059] The lower limit of the screw dislocation ratio is preferably 0.62, more preferably 0.63, and even more preferably 0.65. The upper limit of the screw dislocation ratio is not particularly limited. However, when the contents of each element in the chemical composition of the steel wire are within the range of this embodiment, the upper limit of the screw dislocation ratio is, for example, 0.75, and even more preferably 0.70.
[0060] [Method for measuring screw dislocation ratio] The screw dislocation fraction can be determined by analyzing a line profile obtained by X-ray diffraction measurement and deriving the dislocation density using the modified Williamson-Hall equation.
[0061] First, X-ray diffraction measurement is performed on the steel wire. Specifically, a test piece is taken with a cross section including the central axis of the steel wire (i.e., a cross section parallel to the axial direction) as the measurement surface. The length of the test piece is 30 mm. The measurement point is a depth position of d / 2 from the surface of the steel wire on the measurement surface. Here, d (mm) is the diameter of the steel wire. X-ray diffraction (XRD) is performed on the measurement points to obtain a line profile. In XRD, the radiation source is Cu-Kα radiation, the tube voltage is 50 kV, and the tube current is 300 mA. In addition, the diffraction angle (2θ) is in the range of 30 to 150°, and measurements are made at a pitch of 0.02° for 0.6 seconds per point. The calibration of the peak position corresponding to the diffraction angle is performed by using a Si standard plate to check whether the diffraction peak position of a specific surface is shifted from the reference position. In addition, the half-value width is measured using LaB 6 (Lanthanum hexaboride) is used as a standard sample, and the width spread of the device is measured in advance to perform correction.
[0062] From the obtained line profile, the half-widths of the (111), (200), (211), (220), (310), and (222) diffraction planes are measured. The peaks of the line profile are the superposition of Kα1 and Kα2. Therefore, only the Kα1 peak is extracted. Using the fact that the peak intensity ratio of Kα1 and Kα2 is 2:1, the half-width is derived by fitting from a Lorentzian function. Using the measured half-widths of each diffraction plane, the screw dislocation fraction S is calculated by the modified Williamson-Hall method as follows:
[0063] When discussing the elastic properties of the crystal planes {hkl}, the orientation parameter Γ defined by equation (1) is used. Γ=(h 2 k 2 +k 2 l 2 +l 2 h 2 ) / (h 2 +k 2 +l 2 ) 2 (1) Moreover, the average contrast factor C used in the modified Williamson-Hall method is defined by equation (2). C=0.285(1-qΓ) (2)
[0064] The screw dislocation fraction S can be calculated using q according to formula (3). S = (qq e ) / (q s -q e ) (3) In equation (3), q e is the value when all dislocations in pure iron are edge dislocations, and q e = 1.372. s is the value when all dislocations in pure iron are screw dislocations, and q s =2.652.
[0065] Here, q is calculated by the modified Williamson-Hall equation defined in equation (4). ΔK hkl =α+βK hkl √(C)+γ(K hkl ) 2 C (4) Here, the diffraction angle in the line profile of the {hkl} diffraction plane obtained by XRD is θ hkl (°), half-width is ω hkl (rad), the wavelength of X-ray Kα1 is λ, the crystallite size is D, and the amount of strain around the dislocation line is ε k Then, ΔK in equation (4) hkl and K hkl is defined by equations (5) and (6). ΔK hkl =2sin(θ hkl +ω hkl / 2)-2sin(θ hkl -ω hkl / 2) / λ=0.9 / D+ε k K hkl (5) K hkl =2sinθ hkl / λ (6)
[0066] In formula (4), β and γ are material constants. Here, γ is a very small value compared to β and α. Therefore, the third term on the right side of formula (4) is ignored and formula (7) is used. ΔK hkl=α+βK hkl √(C) (7)
[0067] Here, we move α in equation (7) to the left side and square it to derive equation (8). (ΔK hkl -α) 2 / (K hkl ) 2 =β 2 0.285(1-qΓ) (8)
[0068] Equation (8) shows that a linear relationship is established between the value on the left side and Γ. When the value of α is optimal, the linear relationship between the left side and Γ is optimal. Therefore, an appropriate value is substituted for α to obtain a fitting index that indicates the accuracy of the linear relationship, and the relationship between the value of α and the fitting index is organized to obtain α that provides the best linear relationship. q is obtained using the obtained α and equation (8). The obtained q is substituted into equation (3) to obtain the screw dislocation fraction S. The derivation of the screw dislocation fraction S shown above is also described in Non-Patent Document 1 and Non-Patent Document 2.
[0069] [Effects of the steel wire according to this embodiment] The steel wire of this embodiment satisfies Features 1 to 3. Therefore, an excellent durability ratio can be obtained while having high tensile strength. Preferably, in the steel wire of this embodiment, when the tensile strength is 1600 to 2500 MPa, the durability ratio is 0.25 or more.
[0070] The lower limit of the durability ratio is preferably 0.26, and more preferably 0.27. The upper limit of the durability ratio is not particularly limited. However, when the content of each element in the chemical composition of the steel wire is within the range of this embodiment, the upper limit of the durability ratio is, for example, 0.60, and more preferably 0.50.
[0071] [Applications to which the steel wire of this embodiment can be applied] The steel wire of the present embodiment can be widely used in applications requiring high tensile strength and excellent durability, for example, bead wire, steel cord, bridge wire, wire rope, etc. In the microstructure of the steel wire of the present embodiment, the area ratio of pearlite is 90% or more, preferably 92% or more, and more preferably 95%.
[0072] [One example of the manufacturing method of the steel wire according to this embodiment] An example of a method for manufacturing the steel wire of this embodiment will be described. The method for manufacturing the steel wire described below is one example for manufacturing the steel wire of this embodiment. Therefore, the steel wire having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing the steel wire of this embodiment.
[0073] An example of a method for producing a steel wire according to the present embodiment includes the following steps. (Process 1) Material preparation process (Process 2) Blooming rolling process (Process 3) Finish rolling process (Process 4) Wire drawing process (Step 5) Heat treatment step A wire rod that is a raw material for a steel wire is manufactured in steps 1 to 3. A steel wire is manufactured from the wire rod as a raw material in steps 4 and 5. Each step will be described below.
[0074] [(Process 1) Material preparation process] In the material preparation step, a material for the steel wire of this embodiment is prepared. Specifically, molten steel having a chemical composition that satisfies Feature 1 is produced. The refining method is not particularly limited, and any well-known method may be used. For example, molten iron produced by a well-known method is subjected to refining (primary refining) in a converter. Molten steel tapped from the converter is subjected to well-known secondary refining. Through the above steps, molten steel having a chemical composition that satisfies Feature 1 is produced.
[0075] The produced molten steel is used to produce a material by a known casting method. For example, an ingot may be produced by an ingot casting method using the molten steel. Also, a bloom may be produced by a continuous casting method using the molten steel. By the above-mentioned methods, a material (ingot or bloom) is produced.
[0076] [(Process 2) Blossom rolling process] In the blooming process, the material (ingot or bloom) prepared in the material preparation process is subjected to blooming to produce a billet.
[0077] In the blooming process, first, the material is heated using a heating furnace by a well-known method. The heating temperature is not particularly limited. Any well-known temperature is sufficient. The heating temperature is, for example, 1000 to 1200°C.
[0078] The heated material is hot rolled using a blooming mill, or a blooming mill and a continuous rolling mill, to produce a billet. Specifically, the heated material is reverse rolled using the blooming mill to produce a billet. If a well-known continuous rolling mill is disposed downstream of the blooming mill, the billet after blooming may be further subjected to tandem rolling using the continuous rolling mill to produce a smaller billet.
[0079] [(Process 3) Finish rolling process] In the finish rolling process, the billet produced in the blooming process is subjected to finish rolling to produce a wire rod. In the finish rolling process, the billet produced in the blooming process is first heated in a heating furnace. The heating temperature is 900 to 1150°C.
[0080] The heated billet is subjected to finish rolling (continuous rolling) using a continuous rolling mill to produce a wire rod. The continuous rolling mill includes a plurality of rolling stands arranged in a line from upstream to downstream. Each rolling stand includes a pair of work rolls. Each work roll is formed with a caliber, and the calibers of the pair of work rolls form a groove. The finish rolling temperature in the finish rolling (the temperature at the end of the finish rolling) is 800 to 1000°C. Preferably, the finish rolling step satisfies any condition 1.
[0081] (Condition 1) The cooling process of the wire after coiling is carried out by air blast cooling, and the average cooling rate CR in the temperature range of 750 to 540°C is set to 2 to 30°C / sec.
[0082] The average cooling rate CR in the temperature range of 750 to 540 ° C. affects the lamellar spacing of the pearlite structure of the wire rod, which is the raw material for the steel wire. The lamellar spacing of the wire rod affects the screw dislocation ratio S of the steel wire. If the average cooling rate CR in the temperature range of 750 to 540 ° C. is too small, the lamellar spacing of the wire rod becomes wide. In this case, the edge dislocation density cannot be sufficiently reduced in the heat treatment described below. As a result, the screw dislocation ratio S of the steel wire becomes low. On the other hand, if the average cooling rate CR is too large, some bainite or martensite may appear. If the average cooling rate CR in the temperature range of 750 to 540 ° C. is 2 to 30 ° C. / sec, the lamellar spacing of the pearlite structure of the wire rod can be made to an appropriate width.
[0083] [(Process 4) Wire drawing process] In the wiredrawing process, the produced wire is drawn. The wiredrawing process may be only a primary wiredrawing process, or multiple wiredrawing processes such as a secondary wiredrawing process may be performed. When multiple wiredrawing processes are performed, a well-known patenting process may be performed after each wiredrawing process and before the next wiredrawing process is performed. Preferably, the wiredrawing process satisfies Condition 2.
[0084] (Condition 2) When the diameter before the initial wiredrawing is d0 and the diameter after the final wiredrawing is d1, the distortion amount ε defined by the following formula is 1.5 to 2.5. ε=2×ln(d0 / d1)
[0085] If the strain amount ε is too low, the dislocation density in the steel wire after wiredrawing is too low. In this case, sufficient tensile strength or sufficient screw dislocation ratio S may not be obtained. If the strain amount ε is too high, sufficient screw dislocation ratio S may not be obtained. When the strain amount ε is 1.5 to 2.5, the produced steel wire has an appropriate tensile strength and an appropriate screw dislocation ratio S. When wiredrawing is performed multiple times, the strain amount ε is the total strain amount of the multiple wiredrawing processes, that is, the cumulative strain amount.
[0086] [(Step 5) Heat treatment step] In the heat treatment step, heat treatment is performed on the steel wire after the wire drawing step. The heat treatment may be, for example, a bluing treatment, or a thermal diffusion treatment of electroplating such as hot-dip plating or brass plating. In the heat treatment step, the tensile strength of the steel wire is adjusted and the screw dislocation ratio S is increased. Preferably, the heat treatment step satisfies Conditions 3 to 5. (Condition 3) The heat treatment temperature T (° C.) is 100 to 500° C., and the holding time t (seconds) is 5 to 3600 seconds. (Condition 4) The heat treatment parameter P defined by formula (A) satisfies formula (B). P=(T+273)×(log(t / 60 / 60)+20) (A) RefL≦P≦RefH (B) Here, T in the formula (A) is the heat treatment temperature (° C.), and t is the holding time (seconds) at the heat treatment temperature T. Furthermore, RefL and RefH are defined by the following formulas. RefL=11×10 M1 ×exp(-ε / 2)+7700 RefH=19×10 M2 ×exp(-ε / 2)+12000 Here, M1 and M2 are defined by the following formulas (C) and (D). M1=1.0+0.01×Mn-0.08×Cr-0.002×Si-log((17.8+78.2×C+2.5×CR) / 1000) (C) M2=1.2+0.01×Mn-0.08×Cr-0.002×Si-log((17.8+78.2×C+2.5×CR) / 1000) (D) Here, the content by mass% of the corresponding element in the chemical composition of the steel wire is substituted for each element symbol in formula (C) and formula (D), and the average cooling rate CR (℃ / sec) in the temperature range of 750 to 540°C in the rolling process is substituted for CR. (Condition 5) After holding the heat treatment temperature T (°C) for a holding time t (seconds), the average cooling rate to room temperature is 50°C / second or more.
[0087] [(Condition 4) Heat treatment parameter P] The screw dislocation fraction S of a steel wire is affected by the elements in the chemical composition, particularly the content of Mn, which is an austenite stabilizing element, and C, Si, and Cr, which are elements that enhance hardenability, the lamellar spacing of the wire material that is the raw material for the steel wire, the amount of strain introduced into the steel wire before heat treatment, and the amount of heat introduced into the steel wire by heat treatment.
[0088] If the heat treatment parameter P is less than RefL, edge dislocations do not disappear sufficiently during heat treatment. In this case, the screw dislocation fraction S becomes low. On the other hand, if the heat treatment parameter P exceeds RefH, not only edge dislocations but also screw dislocations disappear during heat treatment. As a result, the screw dislocation fraction S also becomes low in this case. If the heat treatment parameter P satisfies formula (B), the relationship between the chemical composition, lamellar spacing, strain amount, and heat treatment conditions is appropriate. Therefore, the screw dislocation fraction S falls within an appropriate range.
[0089] [(Condition 5) Average cooling rate] If the average cooling rate in the heat treatment process is too slow, screw dislocations may disappear in the steel wire during cooling. This reduces the screw dislocation fraction S of the steel wire. If the average cooling rate is 50°C / sec or more, screw dislocations are less likely to disappear in the steel wire during cooling. As a result, an appropriate screw dislocation fraction S can be obtained.
[0090] The steel wire according to the present embodiment is manufactured by the above manufacturing steps. The above manufacturing method is a preferred example of the manufacturing method of the steel wire according to the present embodiment. Therefore, the steel wire having the above configuration may be manufactured by a manufacturing method other than the above manufacturing method. In short, the manufacturing method is not particularly limited as long as the steel wire of the present embodiment having the above configuration can be manufactured. EXAMPLES
[0091] The effects of the steel wire of the present embodiment will be described more specifically with reference to examples. The conditions in the following examples are one example of conditions adopted to confirm the feasibility and effects of the steel wire of the present embodiment. Therefore, the steel wire of the present embodiment is not limited to this one example of conditions.
[0092] Steel wires having the chemical compositions shown in Tables 1A to 1C were produced by the following method.
[0093] [Table 1A]
[0094] [Table 1B]
[0095] [Table 1C]
[0096] Specifically, a bloom was subjected to a blooming process to produce a billet. Specifically, the bloom was heated to 1000 to 1200°C using a heating furnace. The bloom after heating was hot rolled using a blooming mill and a continuous rolling mill to produce a billet. The billet produced in the blooming process was allowed to cool to room temperature.
[0097] Finish rolling was carried out on the billet. Specifically, the billet was heated to 1000 to 1150°C using a heating furnace. The heated billet was subjected to finish rolling (continuous rolling) using a continuous rolling mill to produce wire rod. The finish rolling temperature was 800 to 1000°C. The average cooling rate CR (°C / sec) between 750°C and 540°C during the cooling process after coiling is shown in Table 2. Note that air blast cooling was carried out during the cooling process after coiling.
[0098] [Table 2]
[0099] The produced wire rod was drawn to produce steel wire. The diameters d0 and d1 (mm) and strain ε of the steel wire before and after the drawing process are shown in Table 2. The steel wire after the drawing process was subjected to heat treatment (blueing treatment). The heat treatment temperature T (℃), holding time t (sec), RefL, heat treatment parameters P, RefH, and average cooling rate after heat treatment (℃ / sec) are shown in Table 2. Steel wires of each test number were produced by the above manufacturing process.
[0100] [About the evaluation test] The following evaluation tests were carried out on the steel wires having each test number. (Test 1) Tensile strength measurement test (Test 2) Measurement test of screw dislocation ratio (Test 3) Durability ratio evaluation test
[0101] [(Test 1) Tensile strength measurement test] The tensile strength of the steel wire of each test number was determined based on the method described in the above [Method of measuring tensile strength]. The obtained tensile strengths are shown in the "Tensile strength (MPa)" column in Table 3.
[0102] [Table 3]
[0103] [(Test 2) Screw dislocation ratio measurement test] Based on the method described in [Method of measuring screw dislocation ratio] above, the screw dislocation ratio S of the steel wire of each test number was determined. The determined screw dislocation ratio S is shown in the "Screw dislocation ratio S" column in Table 3.
[0104] [(Test 3) Evaluation test of durability ratio] The fatigue strength was determined by the following method using the steel wire of each test number. A test piece 200 mm long was taken in the axial direction from an arbitrary position of the steel wire of each test number described above. A fatigue strength test was performed on the test piece in air at room temperature using an axial fatigue testing machine under the following conditions. The test was performed with the chuck distance (length of evaluation part) fixed at 160 mm, frequency at 10 Hz, minimum stress at 50 MPa, and maximum stress varied. The maximum number of repetitions was 2.0 x 106 The number of cycles was determined as the number of times. The maximum stress among the test pieces that survived the maximum number of cycles was defined as the fatigue strength (MPa). The value obtained by dividing the fatigue strength by the tensile strength (= fatigue strength / tensile strength) was defined as the durability ratio. The obtained fatigue strength (MPa) and durability ratio are shown in the "Fatigue strength (MPa)" and "Durability ratio" columns in Table 3.
[0105] [Evaluation test results] With reference to Tables 1A to 1C, Table 2 and Table 3, the steel wires of Test Nos. 1 to 33 satisfied Features 1 to 3. Therefore, the steel wires of these Test Nos. had high strength as well as excellent durability ratios.
[0106] On the other hand, in test numbers 34 and 35, the C content was too low, and therefore the steel wires did not have sufficient tensile strength and durability ratio.
[0107] In the test numbers 36 and 48, the strain amount ε in the wire drawing process was too low. Therefore, the screw dislocation ratio S in the steel wire was low, and a sufficient durability ratio was not obtained.
[0108] In Test Nos. 37 to 39, the heat treatment parameter P was less than RefL. Therefore, the screw dislocation fraction S was low in the steel wire, and a sufficient durability ratio was not obtained.
[0109] In the test numbers 40 and 41, the strain amount ε in the wire drawing process was too high. Therefore, the screw dislocation ratio S in the steel wire was low, and a sufficient durability ratio was not obtained.
[0110] In the test numbers 42 and 49, the holding time t in the heat treatment process was too long. Therefore, the screw dislocation ratio S in the steel wire was low, and a sufficient durability ratio was not obtained.
[0111] In test numbers 43 to 45 and 50, the heat treatment parameter P exceeded RefH. Therefore, the screw dislocation fraction S was low in the steel wires, and a sufficient durability ratio was not obtained.
[0112] In the test numbers 46 and 47, the average cooling rate in the heat treatment process was too slow, so that the screw dislocation fraction S in the steel wire was low and a sufficient durability ratio was not obtained.
[0113] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.
Claims
1. The chemical composition, in mass%, is C: 0.70 to less than 1.10%; Si: 0.10-1.00%, Mn: 0.20-1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, and N: 0.0100% or less; The balance is Fe and impurities. The tensile strength is 1600 to 2500 MPa, The screw dislocation ratio is 0.60 or more. Steel wire.
2. The chemical composition, in mass%, is C: 0.70 to less than 1.10%; Si: 0.10-1.00%, Mn: 0.20-1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, and N: 0.0100% or less; Further, the composition contains one or more selected from the group consisting of Group 1 and Group 2, The balance is Fe and impurities. The tensile strength is 1600 to 2500 MPa, The screw dislocation ratio is 0.60 or more. Steel wire. [Group 1] Cr: 0.50% or less, Co: 0.50% or less, Cu: 0.50% or less, Ni: 0.50% or less, Mo: 0.20% or less, B: 0.0050% or less, W: 0.20% or less, Ti: 0.100% or less, Nb: 0.100% or less, Sn: 0.100% or less, and V: 0.10% or less, one or more selected from the group consisting of [Group 2] Ca: 0.0050% or less, Mg: 0.0050% or less, Zr: 0.010% or less; and Rare earth elements (REM): 0.005% or less, one or more selected from the group consisting of
3. The steel wire according to claim 2, The chemical composition comprises the first group, Steel wire.
4. The steel wire according to claim 2, The chemical composition contains the second group, Steel wire.
Citation Information
Patent Citations
High carbon steel wire rod for steel wire having high strength and high ductility
JP1994049592A
High strength high carbon steel wire excellent in elongation property and manufacture thereof
JP1998305308A